2017
DOI: 10.1007/s12192-017-0795-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative protein modification alters proteostasis under acute hypobaric hypoxia in skeletal muscles: a comprehensive in vivo study

Abstract: While numerous maladies are associated with hypobaric hypoxia, muscle protein loss is an important under studied topic. Hence, the present study was designed to investigate the mechanism of muscle protein loss at HH. SD rats were divided into normoxic rats, while remaining rats were exposed to simulated hypoxia equivalent to 282-torr pressure (equal to an altitude of 7620 m, 8% oxygen), at 25 °C for 6, 12, and 24 h. Post-exposure rats were sacrificed and analysis was performed. Ergo, muscle loss-related change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 63 publications
(69 reference statements)
5
34
0
Order By: Relevance
“…Intracellular Ca 2+ overload can be considered a cause of the increased protein degradation and muscle atrophy characterizing cisplatin-induced cachexia. Indeed, increased intracellular Ca 2+ activates calpains, calcium-activated proteases, that play a pivotal role in the initiation of most proteolytic pathways such as the ubiquitin-proteasome pathway [43]. Furthermore, several studies show that intracellular calcium increase stimulates the mitochondrial apoptotic process through the activation of proapoptotic protein Bax which favors the formation of the mitochondrial permeability transition pore (mPTP) allowing the release of cytochrome C from mitochondria and promoting cell apoptosis [44].…”
Section: Calcium Homeostasismentioning
confidence: 99%
“…Intracellular Ca 2+ overload can be considered a cause of the increased protein degradation and muscle atrophy characterizing cisplatin-induced cachexia. Indeed, increased intracellular Ca 2+ activates calpains, calcium-activated proteases, that play a pivotal role in the initiation of most proteolytic pathways such as the ubiquitin-proteasome pathway [43]. Furthermore, several studies show that intracellular calcium increase stimulates the mitochondrial apoptotic process through the activation of proapoptotic protein Bax which favors the formation of the mitochondrial permeability transition pore (mPTP) allowing the release of cytochrome C from mitochondria and promoting cell apoptosis [44].…”
Section: Calcium Homeostasismentioning
confidence: 99%
“…Shreds of evidence from past studies suggested that an altitude of 5000m and higher (Everest Base camp) led to the considerable deterioration of skeletal muscle tissue [ 1 ]. Our recent study also provided the detailed overview of oxidative protein modification in response to hypobaric hypoxia, which altered muscle protein homeostasis and triggered ER stress [ 2 ]. Although the acute hypoxia exposure was activating several proteolytic pathways, studies have established that prolonged stay at high altitude leads to loss of skeletal muscle mass and a decline in physical performance [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be assumed that under these conditions, TPK activity and immunoreactivity decrease (Fig. 6, B) is partly a consequence of the protein modification due to changes the intracellular redox state [26,27]. These changes are reversible and, as can be seen from the data presented, even with a single thiamine administration, redox state normalization was observed.…”
Section: Fig 5 Immunoreactivity Of Tpk In the Three Brain Regions Omentioning
confidence: 58%